2014
DOI: 10.1371/journal.pone.0110886
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Selenium and Other Micronutrients and Thyroid Cancer Incidence in the NIH-AARP Diet and Health Study

Abstract: BackgroundSelenium is an essential trace element that is important for thyroid hormone metabolism and has antioxidant properties which protect the thyroid gland from oxidative stress. The association of selenium, as well as intake of other micronutrients, with thyroid cancer is unclear.MethodsWe evaluated associations of dietary selenium, beta-carotene, calcium, vitamin D, vitamin C, vitamin E, folate, magnesium, and zinc intake with thyroid cancer risk in the National Institutes of Health – American Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…Moreover, a deficiency in magnesium may be involved in the aetiology of some thyroid diseases . However the protective effects of F&V and fruit juices components are not consistent and several studies showed null results, or even positive associations ( e.g ., with beta‐carotene, vitamin C and flavanones) …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a deficiency in magnesium may be involved in the aetiology of some thyroid diseases . However the protective effects of F&V and fruit juices components are not consistent and several studies showed null results, or even positive associations ( e.g ., with beta‐carotene, vitamin C and flavanones) …”
Section: Discussionmentioning
confidence: 99%
“…In many studies on animal models, as well as in epidemiological and interventional surveys, beneficial effects were confirmed of normal or even increased serum selenium concentrations on the initiation, progression, and even metastases of various cancer types but not of thyroid cancer [50,102]. The relationship between selenium supplementation and the incidence of thyroid cancer has been verified in many clinical studies (Table I); however, it has not been unequivocally confirmed, especially in the Polish population [103][104][105][106][107][108][109][110][111]. The access to mainly retrospective data, the relatively small groups of patients, and the short observation periods, as well as only single assays of selenium concentration levels, were all significant limitations in the performed studies.…”
Section: Prace Poglądowementioning
confidence: 99%
“…W wielu badaniach na modelach zwierzęcych oraz epidemiologicznych i interwencyjnych stwierdzono korzystny wpływ prawidłowych, a nawet podwyższonych stężeń selenu w surowicy na inicjację, progresję, a nawet przerzuty różnych rodzajów nowotworów, ale nie raka tarczycy [50,102]. Związek pomiędzy zaopatrzeniem w selen i występowaniem raka tarczycy został zweryfikowany w wielu badaniach klinicznych (Tabela I) i w metaanalizie, jednakże nie został jednoznacznie potwierdzony, zwłaszcza w polskiej populacji [103][104][105][106][107][108][109][110][111]. Dostęp głównie do danych retrospektywnych, relatywnie małe grupy pacjentów i krótki czas obserwacji oraz pojedyncze oznaczenia zaopatrzenia w selen stanowią istotne ograniczenia przeprowadzonych badań.…”
Section: Prace Poglądoweunclassified
“…25,52,53 Results from human clinical intervention trials support that Se may have chemopreventive effects on lung cancer, especially for subjects with low Se status. 54,55 Although Se is necessary for the metabolism of thyroid hormones and plays an important role in the protection of thyroid gland from OS, 56,57 no strong association has been found between dietary intake of Se and the incidence of thyroid cancer. 57 Similarly, it has also been reported that Se supplementation has no effect on the reduction of bladder cancer incidence, and cannot prevent the recurrence of bladder cancer.…”
Section: The Role Of Se In Cancermentioning
confidence: 99%